Down syndrome : visions for the 21st century - William I. Cohen; Lynn, Nadel; Myra E. Madnick (New York : Wiley-Liss, 2002)
Providing a comprehensive survey of the clinical, educational, developmental, psychosocial, and transitional issues relevant to people with Down syndrome, this book addresses the needs of family members, caregivers, and professionals alike. Edited in association with the National Down Syndrome Society, this up-to-date treatment incorporates the newest developments concerning sexuality, inclusion, transition into adulthood, and legislation, as well as a discussion of the Human Genome Project and the sequencing of chromosome 21.
Includes index.
Keywords: Down syndrome -- rehabilitation; Community Mental Health Services -- trends; Interpersonal Relations; Education, Special -- trends; Patient Participation -- trends